Implementation of Management Strategic Human Resourch for Job Function Standard in Bank Rakyat Indonesia Branch Office Slamet Riyadi, Solo - Supriyadi, Mikhael Ananda; Suprayitno, Suprayitno (Society : Jurnal Pengabdian Masyarakat, 2025)
This article discusses the internship program conducted at Bank Rakyat Indonesia (BRI) Solo Slamet Riyadi Branch from March 1st to May 31st, 2025. The objective of the internship was to observe and analyze the human resource management (HRM) strategies implemented to support the achievement of standard job functions within the Operational Department. The method used was qualitative-descriptive, involving direct observation, participation in administrative activities, and documentation. The results indicate that BRI applies structured HRM strategies such as orientation programs, work mentoring, and systematic task distribution, all of which contribute significantly to the effectiveness and efficiency of employees. The internship also provided valuable insight into the real-world banking environment, highlighting the importance of soft skills, adaptability, and work ethics. In conclusion, well-implemented HRM strategies positively impact job performance standards and prepare students for professional careers.